Isolation of Anti-Escherichia coli O157:H7 Bacteriophages and Determination of Their Host Ranges - Zeliha Yıldırım; Tuba Sakin; Fatma Çoban (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study was to isolate, purify and determine host ranges of bacteriophages infecting Escherichia coli O157:H7 from different environment such as river/stream water, sewage, raw food, animal troughs, wastewaters of food processing plants, slaughterhouse and fish farms. For screening of E. coli O157:H7 bacteriophages, 92 samples were used. It was found that in respect to anti-E. coli O157:H7 bacteriophages, food processing wastewaters, sewage and slaughterhouse wastewaters are the richest sources, and streams, troughs and fisheries wastewater are rich in the middle, and raw foods were the poorest source. A total of 37 phages were isolated and purified. The phages counts of the purified samples were changed among 30×103 - 34×108 PFU/mL. The isolated phages were generally infective against E. coli O157:H7 and E. coli strains and 81.08% of the phages (30 out of 37) formed clear plaques and were capable to lyse at least 1 out of 5 E. coli O157:H7 strains. In addition to E. coli, some phages were capable to infect some Salmonella enterica serovars. This results show that inhibitor spectra of the phages were wide.